Depletion of intracellular Ca2+ induces FOXM1 SUMOylation and accumulation on the inner nuclear membrane and accelerates G2/M cell cycle transition - Tzu-Chien Lin; Ping-Jung Chung; Chen-An Shen; Thi My Hang Nguyen; Yi-Syuan Lin; Shih-Chieh Lin; Shih-Chuan Hsiao; Wen-Tai Chiu (European Journal of Cell Biology, 2023)
Intracellular calcium (Ca2+) has been reported to regulate transcription factor activity and cancer development, but how it affects the function of Forkhead box protein M1 (FOXM1), a crucial transcription factor and key oncogene participating in tumorigenesis, remains unclear. Here, we investigated the regulatory role of Ca2+ on FOXM1 and found that Ca2+ depletion caused the distribution of FOXM1 to aggregate on the nuclear envelope, which was also observed in many cell lines. Further experiments revealed that sequestrated FOXM1 colocalized with lamin B in the inner nuclear membrane (INM) and was affected by the activity of nuclear export protein exportin 1 (XPO1). To investigate how intracellular Ca2+ affects FOXM1, we found that among the posttranscriptional modifications, only SUMOylation of FOXM1 showed a pronounced increase under reduced Ca2+, and suppressed SUMOylation rescued FOXM1 sequestration. In addition, Ca2+-dependent SUMOylated FOXM1 appeared to enhance the G2/M transition of the cell cycle and decrease cell apoptosis. In conclusion, our findings provide a molecular basis for the relationship between Ca2+ signaling and FOXM1 regulation, and we look to elucidate Ca2+-dependent FOXM1 SUMOylation-related biological functions in the future.